SUPREME COURT POLICY IN INCREASING KNOWLEDGE OF RELIGIOUS JUSTICE JUDGES THROUGH THE SHARIA ECONOMIC JUDGE CERTIFICATION PROGRAM - Hasjim, Ilman; Salenda, Kasjim; Jafar, Usman; Sanusi, Nur Taufiq (Jurnal Diskursus Islam, 2022)
This research discusses the Supreme Court's policy of increasing the knowledge of Religious Justice judges through the sharia economic judge certification program. This type of research is descriptive qualitative, a type of research to understand the phenomenon of what the research subject experiences in an exceptional natural context. The natural phenomenon referred to is how there is a relationship between PERMA Number 5 of 2016 concerning Sharia Economic Judge Certification and the Supreme Court's policy in increasing the knowledge of Religious Court judges in the field of Sharia economics, the implementation of certification activities, and the results obtained by judges after participating in the certification program, which is then given meaning. This research location focus of the researcher is the office of the Supreme Court of the Republic of Indonesia, which is domiciled in the Special Capital Region (DKI) Jakarta and Bogor Regency, West Java Province. With a methodological approach, namely case studies, normative approaches, human resources (HR), and sharia economic law approaches—data collection techniques with observation, interviews, and documentation. In addition, this research also uses library research through primary and secondary data—the technique of in-depth data analysis by reducing data, presenting data, and drawing conclusions. The results showed that the Religious Court, the Supreme Court, had done so much that it issued several regulations to support this authority. One of the policies produced was the issuance of Supreme Court Regulation (PERMA) Number 5 of 2016 concerning the Certification of Sharia Economic Judges. With the PERMA issuance, many Religious Court judges have been certified in Sharia Economics after participating in the Sharia Economic Judge Certification Training.